Historical and Contemporary Scientific Data on the Problem of Schizophrenia (Texas Journal of Medical Science, 2022)
Publications were analyzed and the main stages of the historical development of the concept of late schizophrenia were described. Despite the continuing ambiguity of this concept, the possibility of both late manifestation of schizophrenia (after 40 years) and very late (after 60 years) is recognized. The issues of classification, diagnosis, clinic and course of late schizophrenia are considered. The results of modern paraclinical research methods are presented. The relevance and prospects for further study of schizophrenia spectrum disorders at a later age, their possible connection with organic changes in the brain are shown.